SCENARIO METHOD IN ASSESSING THE BANKRUPTCY OF AN ORGANIZATION - Буртовая, Нина (SWorldJournal, 2020)
The article deals with the problem of bankruptcy, which has become even more aggravated during the crisis. A description of the current economic situation in the world caused by the pandemic was given. The author considered the essence of one of the techn